IDENTIFYING SOURCES OF GROUNDWATER IN THE LOWER COLORADO RIVER VALLEY, USA, WITH δ18O, δD, AND 3H: IMPLICATIONS FOR RIVER WATER ACCOUNTING - Guay B.E.; Eastoe Ch.J.; Bassett R.; Long A. (My University, 2006)
Isotope measurements (δ18O, δD, 3H) indicate groundwater origin in the Lower Colorado River Valley (LCRV) and provide an alternative, or supplement, to the US Bureau of Reclamation’s proposed “accounting surface” method. The accounting surface method uses a hydraulic criterion to identify certain wells away from the flood plain that will eventually yield mainstream Colorado River water. New isotope data for 5 surface-water and 18 groundwater sites around Topock Marsh, Arizona, are compared with river-water data (1974–2002) from 11 sites between Utah and Mexico and with groundwater data from previous LCRV studies. Three groundwater sources are repeatedly identified in the LCRV: (1) local recharge derived from precipitation, usually winter rain, plots slightly below the global meteoric water line (GMWL) and has δD values that are 20‰ greater than those of recent river water; (2) “older” (pre-1950) upper basin river-water plots on or near the GMWL, distinct from local rainfall and recent river water; and (3) recent (post-1950) Colorado River water, including Topock Marsh samples, plots below the GMWL along an evaporation trend. Large floods, as in 1983, complicate interpretation by routing less evaporated upper basin water into the LCRV; however, tritium content can indicate the age of a water. River-water tritium has declined steadily from its peak of 716 TU in 1967 to about 11 TU in 2002. Mixtures of all three groundwater sources are common.
Keywords: δ18O; δD; 3H; GROUNDWATER; LOWER COLORADO RIVER; STABLE ISOTOPES; WATER ACCOUNTING